Build your vocabulary 1 : intermediate - Flower, John.; Berman, Michael; Nguyễn Thành Yến (Tp.HCM : Nxb Tp.HCM, 1997)
Using a dictionary; Verb square-1; Time expressions; Plurals; Memory game; Numbers; Parts of the body; Jobs-word formation; Sentence starters-1; Word groups-1.
Keywords: Anh ngữ; English language; Vocabulary; English language -- Vocabulary